Positive Organizational Dynamics in Polish Eco-Entrepreneurship: A Qualitative Study through the Lens of Positive Organizational Scholarship: Exploring Values-Driven Innovation, Resilience, and Leadership in Sustainable Business Practice - Brzozowska, Agnieszka (Journal of Positive Management, 2025)
Purpose: This article explores the internal drivers of eco-entrepreneurial success in Poland through the lens of Positive Organizational Scholarship (POS). It aims to fill the research gap concerning how eco-entrepreneurs not only overcome market barriers but also generate innovation and positive social and environmental impact by mobilizing values, resilience, and authentic leadership. Design/methodology/approach: The study employs a qualitative methodology based on semi-structured interviews with 40 purposively selected Polish eco-entrepreneurs from diverse sectors. Thematic analysis was conducted using an inductive coding approach, with interpretation grounded in the POS framework. Findings: Results indicate that eco-entrepreneurs integrate personal ecological values into business models, driving generativity and innovation. High organizational resilience enables adaptation to crises, while authentic, value-driven leadership fosters trust and engagement. Building positive relationships with customers and partners further strengthens social capital and organizational effectiveness. These internal dynamics are central to sustaining eco-enterprises in challenging environments. Implications/limitations: The findings offer practical recommendations for managers: reinforce positive deviance, foster resilience and authentic leadership, and build value-based organizational cultures. Limitations include the qualitative, cross-sectional design and focus on Poland. Future research should use mixed methods, expand to other contexts, and examine long-term effects of POS-based strategies. Originality/value: This study apply the POS framework to Polish eco-entrepreneurship, providing novel insights into the generative processes and internal capabilities that underpin sustainable business practices. It advances theory and practice by highlighting the centrality of positive organizational dynamics in driving innovation and resilience in green enterprises.